2014
DOI: 10.17826/cutf.82552
|View full text |Cite
|
Sign up to set email alerts
|

Doğal Fermente Olan Sütteki Lactobacillus Spp.16S rRNA Geninin Kısmi Analizi

Abstract: Purpose: The aim of this research is to analysis 16S rRNA gene sequence of Lactobacillus spp. from natural fermented milk. Material and Methods:The methods that used in this study are total DNA isolation using alkaline lysis, PCR amplification carried out using of specific primers, and identification of amplified DNA using sequencing. The result of PCR process is a nuclotide with approximately 585 bp length which contained V1-V3 variable regions. 16S rRNA gene sequence then compared and aligned with existing 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…showed slight mutation or difference in genetic material (DNA) which might be due to difference in environmental conditions of the region or area of isolation, served as a determinant of bacterial identification at both genus and species level (Clarridge, 2004). Kusmiyati et al (2014) isolated lactobacilli from naturally fermented milk product, after 16S rRNA gene sequence analysis and phylogenetic study he found that similar isolates formed sister clad with their respective reference isolate. This showed that after BLAST, phylogenetic tree construction was proved to be a vital tool for proper identification and also for studying sequence similarities and differences among different strains and spp.…”
Section: Discussionmentioning
confidence: 99%
“…showed slight mutation or difference in genetic material (DNA) which might be due to difference in environmental conditions of the region or area of isolation, served as a determinant of bacterial identification at both genus and species level (Clarridge, 2004). Kusmiyati et al (2014) isolated lactobacilli from naturally fermented milk product, after 16S rRNA gene sequence analysis and phylogenetic study he found that similar isolates formed sister clad with their respective reference isolate. This showed that after BLAST, phylogenetic tree construction was proved to be a vital tool for proper identification and also for studying sequence similarities and differences among different strains and spp.…”
Section: Discussionmentioning
confidence: 99%